2016
DOI: 10.1107/s205252061600322x
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the structure of TiBe12

Abstract: There has been considerable controversy regarding the structure of TiBe12, which is variously reported as hexagonal and tetragonal. Lattice dynamics simulations based on density functional theory (DFT) show the tetragonal phase space group I4/mmm to be more stable over all temperatures, while the hexagonal phase exhibits an imaginary phonon mode, which, if followed, would lead to the cell adopting the tetragonal structure. We then report the predicted ground state elastic constants and temperature dependence o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…As shown in Figure 2a, although Be atoms occupy two different positions at the z = 0 and z = 0.5 planes, some are located at the same sites, in accordance with the symmetrical structure of the Be 12 Ti crystal. [23] Sites located in the z = 0 plane are referred to as Be2 while those in the z = 0.5 plane are referred to as Be3. 1), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 2a, although Be atoms occupy two different positions at the z = 0 and z = 0.5 planes, some are located at the same sites, in accordance with the symmetrical structure of the Be 12 Ti crystal. [23] Sites located in the z = 0 plane are referred to as Be2 while those in the z = 0.5 plane are referred to as Be3. 1), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that Be 12 Ti forms a tetragonal lattice structure with I4/mmm symmetry. [23]…”
Section: Introductionmentioning
confidence: 99%
“…The bulk Be 12 Ti has tetragonal symmetry in the space group of I 4 /mmm. 38,39 Ti atoms occupy the Wyckoff position of the 2a lattice site (0, 0, 0), and three symmetrically different Be atoms, which are labeled as Be1, Be2 and Be3, occupy the Wyckoff positions of 8f (0.25, 0.25, 0.25), 8i (0.361, 0, 0) and 8j (0.277, 0.5, 0), respectively. The structure of the unit cell for Be 12 Ti is shown in Fig.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Burr et al reported that the Be–Fe­(-Al) intermetallics have much lower oxygen affinity than metallic Be by calculating solution energies of oxygen . The electronic structure and properties of Be 12 Ti were investigated by DFT calculations. , However, the studies on the electric structure were performed with disordered hexagonal cell with P 4 / mmm symmetry, which is pointed out to be incorrect and unstable. , To the best of our knowledge, no experimental investigation has reported on the electron structure of Be 12 M beryllide (M = Ti, V) until today.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 However, the studies on the electric structure were performed with disordered hexagonal cell with P 4 /mmm symmetry, 21 which is pointed out to be incorrect and unstable. 13,22 To the best of our knowledge, no experimental investigation has reported on the electron structure of Be 12 M beryllide (M = Ti, V) until today. This study aims to (i) clarify the valence electron structure of Be 12 M (M = Ti, V) and (ii) perform compositional microanalysis of oxidized beryllide based on the information on electron structure.…”
Section: ■ Introductionmentioning
confidence: 99%